Potential novel inhibitors of trypanosomatid phosphoglycerate mutases through ligand-based and structure-based in silico approaches - Ahmad Fuad, Fazia Adyani; Walkinshaw, Malcolm D.; Fothergill-Gilmore, Linda A.; Houston, Dr. (Academy of Medicine, Singapore, 2015)
Background & Hypothesis: The parasitic protozoa from the order Trypanosomatida relies exclusively on glycolysis for its survival in the mammalian hosts. As a corollary, the enzymes in this pathway have been recognised as chemotherapeutic targets. Phosphoglycerate mutase (iPGAM), which is the seventh enzyme in the pathway, is of particular interest because it possesses no structural and biochemical relationship with the corresponding enzyme in human. This enzyme has also been validated as an attractive therapeutic target for the treatment of trypanosomatid diseases. The aim of this work is to identify small molecules or compounds that could potentially be developed into potent inhibitors of trypanosomatid iPGAMs through in silico approaches. Methods: In the search for novel inhibitors, a ligand-based virtual screening programme, Ultra Fast Shape Recognition with Atom Types (UFSRAT), was utilised to screen for compounds resembling the substrate/product of iPGAM (3-phosphoglycerate/2phosphoglycerate), before a structure-based approach was applied using AutoDock Vina and COmbining Docking And Similarity Search (CODASS) programmes. The inhibitory effects of selected compounds were subsequently tested by monitoring the oxidation of nicotinamide adenine dinucleotide (NADH) through a continuous coupled assay system. Results: The results revealed that out of this collection of compounds, 7 compounds inhibited iPGAM's activity, with 1 compound from virtual screening analysis exhibited substantial inhibition (14% remaining activity). Discussion & Conclusion: Taken together, the findings from this study indicate that compounds which were discovered through in silico approaches have potentials to be developed as novel drugs that specifically target trypanosomatid iPGAMs.